Post-Occupancy Evaluation of the Kudus City Walk Area in Kudus Regency - Khamid, Muhamad Irfan; Avivah, Umi Nur (Journal of Transformative Governance and Social Justice, 2025)
This study presents an indicative-level Post-Occupancy Evaluation (POE) of Kudus City Walk in Central Java, Indonesia, to assess the effectiveness of the public space following its activation. Using a mixed-method approach, data were collected through field observations, structured surveys (n = 30), and semi-structured interviews with visitors and street vendors. The evaluation covered five core POE dimensions: physical quality, accessibility, user comfort, socio-economic functionality, and visitor perception. Results indicate that while Kudus City Walk has succeeded in attracting visitors and supporting street-level economic activity (with high scores in “street vendor count” = 4.2 and “visitor volume” = 4.0), several spatial and managerial shortcomings remain. The lowest-rated indicators were “accessibility for disabled and elderly” (2.3) and “spatial conflicts” (2.5), revealing critical issues in inclusive design and circulation. Qualitative insights confirm the need for more seating, improved lighting, and clearer zoning between pedestrians and vendors. The findings underscore the importance of user-centered design and inclusive planning in sustaining the long-term functionality of hybrid pedestrian-commercial corridors. This study contributes empirical evidence to the limited literature on POE in medium-sized Indonesian cities and offers practical implications for policymakers in optimizing urban public space governance.